Humanizing the comprehensive care system: From political discourse to the defense of the human rights of survivors - Barrantes, Carmen Luisa (2022)
Research on the social representations of survivors of trafficking for sexual exploitation and of those who administer justice and assume their guardianship and care provides information on their impact on life after rescue. The centralityof prejudice regarding sexual exploitation is a common element among all the actors. Another common element is the partial transfer of responsibility for the crime to the survivor and their families, blaming the former for their behavior and the latter for their carelessness. Responsibilities are individualized and the issue is depoliticized, freeing the State from its responsibility for generating conditions that are conducive to human trafficking. After their rescue, a new asymmetric power relationship subordinates and revictimizes them by limiting their human rights under the argument of protecting them.